PbO-M / copper hydrogen storage catalyst, preparation method thereof and application of PbO-M / copper hydrogen storage catalyst in electro-synthesis of sodium borohydride
By loading PbO and M components on the copper surface, the PbO-M/copper catalyst solves the problem of insufficient activity and stability of existing catalysts, and achieves the effect of efficient electroreduction of sodium metaborate to sodium borohydride.
Patent Information
- Application Number
- CN202511254842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-09-04
AI Technical Summary
Existing catalysts have low catalytic activity and poor stability in the process of electroreduction of sodium metaborate to synthesize sodium borohydride, which makes it difficult to meet the demand for efficient regeneration of sodium borohydride.
Using PbO-M/copper hydrogen storage catalyst, PbO and M components (Fe, Co, Ni) are loaded on the copper surface by anodic electrodeposition. PbO is used to promote the breaking of B-OH bonds, and the M component provides an additional H* source to improve the electroreduction selectivity and rate.
High catalytic activity and stability are achieved, the conversion rate and hydrogen storage performance of sodium borohydride are improved, and energy consumption is reduced.
Smart Images

Figure CN120738700A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic regeneration of hydrogen storage materials, and particularly relates to a PbO-M / copper hydrogen storage catalyst, a preparation method thereof, and application in the electrosynthesis of sodium borohydride. Background Art
[0002] Sodium borohydride (NaBH4) is an excellent hydrogen storage material with a hydrogen storage density of up to 10.8 wt%. The product is pollution-free and the hydrogen released is of high purity. It is also a promising candidate for hydrogen storage in direct borohydride fuel cell (DBFC) systems. However, it is expensive and difficult to regenerate.
[0003] Electroreduction of sodium metaborate to sodium borohydride has been a key research focus in the past decade as a regenerative route for sodium borohydride. However, this reaction requires a highly efficient catalyst to reduce the reaction overpotential.
[0004] Researchers have developed some catalysts for the electroreduction of sodium metaborate to synthesize sodium borohydride, but these catalysts have low catalytic activity and poor stability. Summary of the Invention
[0005] The present invention aims to provide a PbO-M / copper hydrogen storage catalyst, a preparation method thereof, and application in the electrosynthesis of sodium borohydride. The PbO-M / copper hydrogen storage catalyst provided by the present invention has good catalytic activity and high stability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The invention provides a PbO-M / copper hydrogen storage catalyst, comprising copper, and PbO and M components supported on the surface of the copper; the M component comprises one or more of Fe, Co and Ni.
[0007] Preferably, the copper is a copper sheet, the thickness of the copper sheet is 10-1000 μm, and the area of the copper sheet is 1-10000 cm 2 .
[0008] Preferably, the PbO loading on the copper surface is 0.01-100 mg / cm 2 .
[0009] Preferably, the molar ratio of the Pb element in the PbO on the copper surface to the M element in the M component is 0.01-1000:1.
[0010] The present invention also provides a method for preparing the PbO-M / copper hydrogen storage catalyst described in the above scheme, which is prepared by anodic electrodeposition on an electrochemical workstation.
[0011] Preferably, the anodic electrodeposition method comprises the following steps: connecting copper to the counter electrode of an electrochemical workstation, using nickel foam as the working electrode and saturated calomel as the reference electrode, and performing constant potential electrodeposition in an electrolyte; the electrolyte comprises Pb salt and M salt, and the pH value is 3~4.
[0012] Preferably, the concentration of the Pb salt in the electrolyte is 10-40 mM, and the concentration of the M salt in the electrolyte is not greater than 50 mM.
[0013] Preferably, the potential of the electrodeposition relative to the reference electrode is 0.1-0.4 V (vs. SCE), the electrodeposition time is 10-60 min, and the electrodeposition temperature is 20-50°C.
[0014] The present invention also provides the use of the PbO-M / copper hydrogen storage catalyst described in the above scheme or the PbO-M / copper hydrogen storage catalyst obtained by the preparation method described in the above scheme in the electrosynthesis of sodium borohydride.
[0015] Preferably, the application method comprises the following steps: using a PbO-M / copper hydrogen storage catalyst as a cathode and a graphite rod as an anode to electrolyze a sodium metaborate alkaline solution; the concentration of sodium metaborate in the sodium metaborate alkaline solution is 0.1~3M, and the concentration of sodium hydroxide is 1~5M.
[0016] The present invention provides a PbO-M / copper hydrogen storage catalyst. A PbO active component is synthesized on copper, which is highly selective for the electroreduction of sodium metaborate to sodium borohydride. By adding elemental M (Fe, Co, Ni) as an additive to the PbO-M / copper hydrogen storage catalyst, the high hydrogen evolution activity of the M element is utilized to controllably enhance the selectivity of the PbO-M / copper hydrogen storage catalyst for the electroreduction of sodium metaborate, thereby increasing the reaction rate of the electroreduction of sodium metaborate to sodium borohydride.
[0017] This invention utilizes the synergistic effect of PbO and M components to produce a PbO-M / copper hydrogen storage catalyst with high selectivity for the electroreduction of sodium metaborate. The structural formula of sodium metaborate in aqueous solution is actually NaB(OH)4. The mechanism of action of PbO is to promote the breakage of the boron-oxygen bond in B-OH. In addition, because Pb has a high hydrogen evolution potential, it can increase the selectivity of the sodium metaborate electroreduction reaction (making the electroreduction reaction the primary reaction and the electrolysis of water hydrogen evolution as a secondary reaction). The role of the auxiliary metal component M is to promote the dissociation and adsorption of water molecules in the electrolysis of water hydrogen evolution reaction, providing additional H for the sodium metaborate electroreduction reaction. * Source, and due to the weak electrochemical desorption or chemical desorption ability of the M component, the two H * It is difficult to combine to generate H2 desorption, and the additional H provided by the side reaction * The source can be fully utilized by the electroreduction reaction.
[0018] The present invention also provides a method for preparing the PbO-M / copper hydrogen storage catalyst described in the above scheme. This method uses anodic electrodeposition to cause metal cations in solution to undergo an oxidation reaction on the anode surface, losing electrons to form insoluble compounds that are then deposited. This method features simple steps, easy-to-control operations, and promising prospects for large-scale application.
[0019] The present invention also provides the use of the PbO-M / copper hydrogen storage catalyst described in the above scheme, or the PbO-M / copper hydrogen storage catalyst obtained by the preparation method described in the above scheme, in the electrosynthesis of sodium borohydride. The PbO-M / copper hydrogen storage catalyst provided by the present invention can achieve a fast sodium borohydride conversion rate, low energy consumption, and excellent hydrogen storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 Schematic diagram of the process of preparing PbO-M / copper hydrogen storage catalyst by anodic electrodeposition method in the present invention; Figure 2 This is a SEM image of the PbO-Fe / copper hydrogen storage catalyst prepared in a 15 mM FeCl3 electrolyte according to Example 1; Figure 3 Linear voltammetric scans of the PbO-M / copper hydrogen storage catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 in sodium metaborate alkaline solution; wherein (a) is a comparison of the test results of Example 1 and Comparative Example 1, (b) is a comparison of the test results of Example 2 and Comparative Example 2, (c) is a comparison of the test results of Example 3 and Comparative Example 3, and (d) is a graph showing the relationship between the concentration of the M salt and the reduction peak current density; Figure 4 This is a fitting diagram of the reduction peak current density and potential corresponding to the linear voltammetric scan results of the PbO-Co / copper hydrogen storage catalyst prepared at different electrodeposition potentials in sodium metaborate alkaline solution in Example 4; Figure 5 5 is a fitting graph of the reduction peak current density and time corresponding to the linear voltammetric scan results of the PbO-Co / copper hydrogen storage catalyst prepared at different electrodeposition times in sodium metaborate alkaline solution in Example 5; Figure 6 The linear voltammetric scan diagrams of the catalysts of Comparative Examples 1 to 6 in sodium metaborate alkaline solution are shown. DETAILED DESCRIPTION
[0022] The invention provides a PbO-M / copper hydrogen storage catalyst, comprising copper, and PbO and M components supported on the surface of the copper; the M component comprises one or more of Fe, Co and Ni.
[0023] In the present invention, the copper may be a copper sheet, the thickness of which may be 10 to 1000 μm, specifically 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm or 900 μm; the area of the copper sheet may be 1 to 10,000 cm 2 , specifically 10 cm 2 , 50 cm 2 , 100 cm 2 , 500 cm 2 , 1000 cm 2 or 5000 cm 2 .
[0024] In the present invention, the PbO loading on the copper surface is 0.01-100 mg / cm 2 , specifically 0.1 mg / cm 2 , 0.5 mg / cm 2 , 1 mg / cm 2 , 2 mg / cm 2 , 5 mg / cm 2 , 10 mg / cm 2 , 20 mg / cm 2 , 40 mg / cm 2 、60 mg / cm 2 or 80 mg / cm 2 .
[0025] In the present invention, the molar ratio of the Pb element in the PbO on the copper surface to the M element in the M component can be 0.01-1000:1, specifically 0.1:1, 0.5:1, 1:1, 10:1, 50:1, 100:1 or 500:1.
[0026] The present invention also provides a method for preparing the PbO-M / copper hydrogen storage catalyst described in the above scheme, which is prepared by anodic electrodeposition on an electrochemical workstation.
[0027] In the present invention, the anodic electrodeposition method may include the following steps: connecting copper to the counter electrode (anode) of an electrochemical workstation, using nickel foam as the working electrode (cathode), and using saturated calomel as the reference electrode, and performing constant potential electrodeposition in an electrolyte; the electrolyte includes Pb salt and M salt, and the pH value is 3-4.
[0028] In the present invention, the electrolyte can be allowed to stand in a constant-temperature water bath before use; the standing time can be 10 minutes. This standing time preheats the electrolyte to the electrodeposition temperature, aligning it with the water bath temperature, thereby improving the bonding strength and consistency of the PbO-M / copper hydrogen storage catalyst electrogrown particles.
[0029] In the present invention, the pH value of the electrolyte can be adjusted by acid; the acid can be hydrochloric acid.
[0030] In the present invention, the copper may be pretreated before use. The pretreatment may include the following steps: using sandpaper to grind the copper surface into a grid pattern in both the horizontal and vertical directions; the sandpaper may have a mesh size of 100 or less; and the grinding time may be 5 minutes. This pretreatment removes oxides from the copper surface, increases its surface roughness, and improves the bonding strength between the electrodeposition support and the catalyst.
[0031] In the present invention, the copper can be clamped by an electrode clamp and connected to the counter electrode of the electrochemical workstation.
[0032] In the present invention, the volume of the nickel foam may be consistent with that of the copper.
[0033] In the present invention, the volume of the electrolyte is 10~5000 mL, specifically 50 mL, 200 mL, 500 mL, 1000 mL, 2000 mL, 3000 mL or 4000 mL; the total concentration is 10~90 mM, specifically 20 mM, 30 mM, 40 mM, 50 mM, 60 mM, 70 mM or 80 mM; the pH value is 3.0~4.0, specifically 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 or 3.9.
[0034] In the present invention, the concentration of Pb salt in the electrolyte may be 10-40 mM, specifically 15 mM, 20 mM, 25 mM, 30 mM or 35 mM, and the concentration of M salt may be no more than 50 mM, specifically 5 mM, 10 mM, 20 mM, 25 mM, 30 mM or 40 mM.
[0035] In the present invention, the Pb salt in the electrolyte may be lead chloride; the M salt in the electrolyte may include one or more of an Fe salt, a Co salt, and a Ni salt; the Fe salt may be a soluble Fe salt; the soluble Fe salt may include one or both of ferric chloride and ferrous sulfate; the Co salt may be a soluble Co salt; the soluble Co salt may include one or more of cobalt chloride and cobalt sulfate; the Ni salt may be a soluble Ni salt; the soluble Ni salt may include one or more of nickel chloride and nickel sulfate.
[0036] In the present invention, the potential of the electrodeposition relative to the reference electrode can be 0.1~0.4 V (vs. SCE), specifically 0.15 V, 0.20 V, 0.25 V, 0.30 V or 0.35 V; the electrodeposition time can be 10~60 min, specifically 20 min, 30 min, 40 min or 50 min; the electrodeposition temperature can be 20~50 ℃, specifically 25 ℃, 30 ℃, 35 ℃, 40 ℃ or 45 ℃.
[0037] In the present invention, after the electrodeposition, the obtained electrodeposited product may be washed with water and then dried; the washing water may be deionized water; the drying may be oven drying; the drying temperature may be 50° C., and the holding time may be 6 hours.
[0038] The present invention also provides the use of the PbO-M / copper hydrogen storage catalyst described in the above scheme or the PbO-M / copper hydrogen storage catalyst obtained by the preparation method described in the above scheme in the electrosynthesis of sodium borohydride.
[0039] In the present invention, the application method may include the following steps: using a PbO-M / copper hydrogen storage catalyst as a cathode and a graphite rod as an anode to electrolyze a sodium metaborate alkaline solution; In the present invention, the volume of the sodium metaborate alkaline solution may be 10-1000 mL, specifically 50 mL, 100 mL, 200 mL, 400 mL, 600 mL or 800 mL.
[0040] In the present invention, the concentration of sodium metaborate in the sodium metaborate alkaline solution can be 0.1~3 M, specifically 0.5 M, 1.0 M, 1.5 M, 2.0 M or 2.5 M, and the concentration of sodium hydroxide can be 1~5 M, specifically 1.5 M, 2.0 M, 2.5 M, 3.0 M, 3.5 M, 4.0 M or 4.5 M.
[0041] In the present invention, the electrolysis voltage can be 2.5~10 V, specifically 3 V, 4 V, 5 V, 6 V, 7V, 8 V or 9 V; the electrolysis time can be 0.1~24 h, specifically 0.5 h, 2 h, 4 h, 8 h, 16 h or 20 h; the electrolysis temperature can be 25 °C.
[0042] In order to further illustrate the present invention, the scheme of the present invention is described in detail below with reference to the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0043] Example 1 In this example, copper sheets were used to prepare PbO-M / copper hydrogen storage catalysts. The process was as follows: Figure 1 As shown, the specific steps are as follows: A 50 mL electrolyte solution containing PbCl₂ (25 mM) and FeCl₃ (5, 10, 15, 20, or 25 mM) was placed in a constant-temperature water bath and allowed to stand for 10 minutes. The pH was adjusted to 4.0. A 1 cm x 1 cm, 500 μm thick copper sheet was then clamped with an electrode clamp and connected to the counter electrode (anode) of an electrochemical workstation. A nickel foam of the same size as the copper sheet served as the working electrode (cathode), and saturated calomel was used as the reference electrode. The electrodeposition potential was set at 0.34 V, the deposition time was 30 minutes, and the deposition temperature was 35°C. After the electrodeposition, the copper sheet was removed from the counter electrode, rinsed with deionized water, and dried in a 50°C drying oven for 6 hours to obtain the PbO-Fe / copper hydrogen storage catalyst.
[0044] The SEM image of the PbO-Fe / copper hydrogen storage catalyst synthesized in the FeCl3 electrolyte with a concentration of 15 mM is shown in FIG. Figure 2 shown.
[0045] according to Figure 2 , it can be seen that the PbO-Fe / copper hydrogen storage catalyst has a lamellar structure.
[0046] Example 2 In this example, copper sheets were used to prepare PbO-M / copper hydrogen storage catalysts. The specific steps were as follows: A 50 mL electrolyte solution containing PbCl2 (25 mM) and CoCl2 (5, 10, 15, 20, or 25 mM) was placed in a constant-temperature water bath and allowed to stand for 10 minutes. The pH was adjusted to 4.0. A 1 cm x 1 cm, 500 μm thick copper sheet was then clamped with an electrode clamp and connected to the counter electrode of an electrochemical workstation. A nickel foam of the same size as the copper sheet was used as the working electrode, and saturated calomel was used as the reference electrode. The electrodeposition potential was set at 0.34 V, the deposition time was 30 minutes, and the deposition temperature was 35°C. After the electrodeposition, the copper sheet was removed from the counter electrode, rinsed with deionized water, and dried in a 50°C drying oven for 6 hours to obtain the PbO-Co / copper hydrogen storage catalyst.
[0047] Example 3 In this example, copper sheets were used to prepare PbO-M / copper hydrogen storage catalysts. The specific steps were as follows: A 50 mL electrolyte solution containing PbCl2 (25 mM) and NiCl2 (5, 10, 15, 20, or 25 mM) was placed in a constant-temperature water bath and allowed to stand for 10 minutes. The pH was adjusted to 4.0. A 1 cm x 1 cm, 500 μm thick copper sheet was then clamped with an electrode clamp and connected to the counter electrode of an electrochemical workstation. A nickel foam of the same size as the copper sheet was used as the working electrode, and saturated calomel was used as the reference electrode. The electrodeposition potential was set at 0.34 V, the deposition time was 30 minutes, and the deposition temperature was 35°C. After the electrodeposition, the copper sheet was removed from the counter electrode, rinsed with deionized water, and dried in a 50°C drying oven for 6 hours to obtain the PbO-Ni / copper hydrogen storage catalyst.
[0048] Example 4 In this example, copper sheets were used to prepare PbO-M / copper hydrogen storage catalysts. The specific steps were as follows: A 50 mL electrolyte solution containing 25 mM PbCl₂ and 25 mM CoCl₂ was placed in a constant-temperature water bath and allowed to stand for 10 minutes. The pH was adjusted to 3.88. A 1 cm x 1 cm, 500 μm thick copper sheet was then clamped with an electrode clamp and connected to the counter electrode of an electrochemical workstation. A nickel foam of the same size as the copper sheet was used as the working electrode, and saturated calomel was used as the reference electrode. The electrodeposition potential was set at 0.22 V, 0.24 V, 0.25 V, 0.26 V, 0.28 V, 0.30 V, or 0.32 V (vs. SCE) for 30 minutes at a temperature of 35°C. After electrodeposition, the copper sheet was removed from the counter electrode, rinsed with deionized water, and dried in a 50°C drying oven for 6 hours to obtain the PbO-Co / copper hydrogen storage catalyst.
[0049] Example 5 In this example, copper sheets were used to prepare PbO-Co / copper hydrogen storage catalysts. The specific steps were as follows: A 50 mL electrolyte solution containing 25 mM PbCl₂ and 25 mM CoCl₂ was placed in a constant-temperature water bath and allowed to stand for 10 minutes. The pH was adjusted to 3.9. A 1 cm x 1 cm, 500 μm thick copper sheet was then clamped with an electrode clamp and connected to the counter electrode of an electrochemical workstation. A nickel foam of the same size as the copper sheet was used as the working electrode, and saturated calomel was used as the reference electrode. The electrodeposition potential was set at 0.25 V (vs. SCE) for 10, 15, 20, 25, or 30 minutes at a temperature of 35°C. After electrodeposition, the copper sheet was removed from the counter electrode, rinsed with deionized water, and dried in a 50°C drying oven for 6 hours to obtain the PbO-Co / copper hydrogen storage catalyst.
[0050] Example 6 The preparation method of this embodiment is the same as that of Example 1, except that ferric chloride is replaced by ferrous sulfate.
[0051] Example 7 The preparation method of this embodiment is the same as that of Example 2, except that cobalt chloride is replaced by cobalt sulfate.
[0052] Example 8 The preparation method of this embodiment is the same as that of Example 1, except that nickel chloride is replaced by nickel sulfate.
[0053] Comparative Example 1 The preparation method of this comparative example is the same as that of Example 1, except that FeCl3 is not added.
[0054] Comparative Example 2 The preparation method of this comparative example is the same as that of Example 2, except that CoCl2 is not added.
[0055] Comparative Example 3 The preparation method of this comparative example is the same as that of Example 3, except that NiCl2 is not added.
[0056] Comparative Example 4 The preparation method of this comparative example is the same as that of Example 1, except that no PbCl2 is added.
[0057] Comparative Example 5 The preparation method of this comparative example is the same as that of Example 2, except that no PbCl2 is added.
[0058] Comparative Example 6 The preparation method of this comparative example is the same as that of Example 3, except that no PbCl2 is added.
[0059] Comparative Example 7 The preparation method of this comparative example is the same as that of Example 1, except that ferric chloride is replaced by sodium tungstate.
[0060] Comparative Example 8 The preparation method of this comparative example is the same as that of Example 2, except that ferric chloride is replaced by sodium molybdate.
[0061] Comparative Example 9 The preparation method of this comparative example is the same as that of Example 3, except that cobalt chloride is replaced by titanium sulfate.
[0062] Test Example 1 The PbO-Co / copper hydrogen storage catalysts prepared in Examples 1 to 3 and the catalysts prepared in Comparative Examples 1 to 3 were subjected to a performance test of the catalytic electroreduction reaction of sodium metaborate to synthesize sodium borohydride. The test method is as follows: the PbO-M / copper hydrogen storage catalysts prepared in Examples 1, 2 or 3 or the catalysts prepared in Comparative Examples 1, 2 or 3 are used as working electrodes, a mercury-mercuric oxide electrode is used as a reference electrode, and a graphite electrode is used as a counter electrode. In a 0.5 M NaBO2 + 1 M NaOH solution, the reduction peak current density during the negative sweep process is tested by linear voltammetry or cyclic voltammetry. The greater the reduction peak current density, the faster the sodium metaborate electroreduction reaction rate, and the more sodium borohydride is generated per unit time during actual application of the catalyst, which proves that the hydrogen storage performance of the PbO-M / copper catalyst is better. The test results are as follows: Figure 3 shown.
[0063] The test results of Example 1 and Comparative Example 1 are as follows Figure 3 As shown in (a), it can be seen that the performance of the PbO-Fe / copper hydrogen storage catalyst prepared by using electrolytes with different FeCl3 concentrations is better than that without adding FeCl3; the test results of Example 2 and Comparative Example 2 are shown in FIG. Figure 3 As shown in (b), it can be seen that the performance of the PbO-Co / copper hydrogen storage catalyst prepared by using electrolytes with different CoCl2 concentrations is better than that without adding CoCl2; the test results of Example 3 and Comparative Example 3 are shown in FIG. Figure 3 As shown in (c), it can be seen that the performance of PbO-Ni / copper hydrogen storage catalysts prepared with different NiCl2 concentration electrolytes is better than that without adding NiCl2; Figure 3 As can be seen from (d) in the figure, Fe and Co have better performance than Ni as additives.
[0064] The same test was performed on the catalysts of Comparative Examples 4 to 6 using the above test method. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that when the electrolyte contains only Fe, Co or Ni components, the catalyst is completely inactive in the electroreduction reaction of sodium metaborate. At this time, only hydrogen evolution reaction occurs during water electrolysis, and no reduction peak appears in the performance test, indicating that PbO is the main active ingredient and Fe, Co or Ni components are active additives.
[0065] The catalysts of Comparative Examples 7 to 9 were tested in the same manner using the above test method. The test results showed that Comparative Examples 7 to 9 were hydrogen storage catalysts synthesized with W, Mo, or Ti as additives. Their performance was inferior to that of the PbO-M / copper hydrogen storage catalysts prepared in Examples 1 to 3, but similar to that of Comparative Example 1, indicating that the use of W, Mo, or Ti elements as additives did not significantly improve the electroreduction reaction rate, and even reduced the electroreduction reaction rate. This is because the adsorbed hydrogen formed on the W, Mo, or Ti metal active sites during the Volmer step (discharge step) of hydrogen evolution during water electrolysis is more easily combined with H2 and desorbed compared to the Fe, Co, or Ni metal active sites, resulting in W, Mo, and Ti as additives being unable to provide additional H2 for the electroreduction reaction. * The above results prove that Pb does not have a synergistic effect with any metal, and the synergistic effect between Pb and M components is specific.
[0066] Test Example 2 The reduction peak current density of the PbO-Co / copper hydrogen storage catalyst prepared at different electrodeposition potentials in Example 4 was fitted, and the results were as follows: Figure 4 shown.
[0067] according to Figure 4 , it can be seen that the PbO-Co / Cu hydrogen storage catalyst prepared at 0.25 V has the best performance.
[0068] Test Example 3 The reduction peak current density of the PbO-Co / copper hydrogen storage catalyst prepared at different electrodeposition times in Example 5 was fitted, and the results are as follows: Figure 5 shown.
[0069] according to Figure 5 It can be seen that the PbO-Co / copper hydrogen storage catalyst prepared in 30 min has the best performance.
[0070] As can be seen from the above examples, the PbO-Co / copper hydrogen storage catalyst provided by the present invention synthesizes PbO on the copper surface and is highly selective for the electroreduction of sodium metaborate to sodium borohydride. By adding the M component, the selectivity of the electroreduction reaction can be further improved, thereby increasing the reaction rate.
[0071] Although the above embodiment provides a detailed description of the present invention, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A PbO-M / copper hydrogen storage catalyst, characterized in that The invention comprises copper, PbO and M components loaded on the surface of the copper; the M component comprises one or more of Fe, Co and Ni.
2. The PbO-M / copper hydrogen storage catalyst according to claim 1, characterized in that The copper is a copper sheet with a thickness of 10-1000 μm and an area of 1-10000 cm 2 .
3. The PbO-M / copper hydrogen storage catalyst according to claim 1 or 2, characterized in that The PbO loading on the copper surface is 0.01~100 mg / cm 2 .
4. The PbO-M / copper hydrogen storage catalyst according to claim 1, characterized in that The molar ratio of the Pb element in the PbO on the copper surface to the M element in the M component is 0.01-1000:
1.
5. The method for preparing the PbO-M / copper hydrogen storage catalyst according to any one of claims 1 to 4, characterized in that: It was prepared by anodic electrodeposition on an electrochemical workstation.
6. The preparation method according to claim 5, characterized in that The anodic electrodeposition method comprises the following steps: The copper was connected to the counter electrode of the electrochemical workstation, nickel foam was used as the working electrode, and saturated calomel was used as the reference electrode, and constant potential electrodeposition was performed in an electrolyte; the electrolyte included Pb salt and M salt, and the pH value was 3-4.
7. The preparation method according to claim 6, characterized in that The concentration of the Pb salt in the electrolyte is 10-40 mM, and the concentration of the M salt is not greater than 50 mM.
8. The preparation method according to claim 6 or 7, characterized in that The potential of the electrodeposition relative to the reference electrode is 0.1-0.4 V, the electrodeposition time is 10-60 min, and the electrodeposition temperature is 20-50°C.
9. Use of the PbO-M / copper hydrogen storage catalyst according to any one of claims 1 to 4 or the PbO-M / copper hydrogen storage catalyst obtained by the preparation method according to any one of claims 5 to 8 in the electrosynthesis of sodium borohydride.
10. The use according to claim 9, characterized in that The application method comprises the following steps: using a PbO-M / copper hydrogen storage catalyst as a cathode and a graphite rod as an anode to electrolyze a sodium metaborate alkaline solution; the concentration of sodium metaborate in the sodium metaborate alkaline solution is 0.1-3 M, and the concentration of sodium hydroxide is 1-5 M.
Citation Information
Patent Citations
Coated composite anodes
CA2907805A1
Method for preparing 2, 6-ditertiary butyl-4-methylphenol by electrochemically degrading lignin
CN103074639A
Metal-air battery based on silver-copper catalysis and preparation method thereof
CN104538709A
Hierarchical structure sodium borohydride hydrogen production catalyst and preparation method and application thereof
CN114618539A
Membrane electrode material for sodium borohydride hydrogen storage prepared by electrolyzing sodium metaborate and process
CN114921807A